The Influence of Government Policies on the Digital Platform Kedai Elektronik Medan (KEDAN) to Facilitate the Marketing of MSMEs Products in the City of Medan - Rahmah, Hajrah; Nasution, Muhammad Irwan Padli; Nurbaiti, Nurbaiti (Quantitative Economics and Management Studies, 2024)
This study aims to evaluate the effect of the expansion policy of the KEDAN digital platform managed by the Medan City Government on the marketing of MSME products in Medan City. The main focus of the research is to identify the level of satisfaction of MSME players with the marketing of their products through this digital platform and analyze how the policies that have been implemented by the local government affect the marketing outcomes. This research uses a quantitative approach with simple linear regression analysis to describe the characteristics of the sample, as well as inferential analysis using SPSS version 29. The research population consists of MSME players who are eligible to transact on the KEDAN digital platform, with a total of 120 respondents in this survey. The results showed that most MSME players in Medan City were satisfied with the marketing of their products through the KEDAN digital platform, with the satisfaction level reaching 95%. Regression analysis showed a positive relationship between the Government's policy towards KEDAN's digital platform and increased marketing of MSME products in Medan City.